An Assessment of Rainfall Variability and Trends in Wukari, Nigeria from 1981 to 2021 - Omopekunola, Moses Oluoke; Jacob, Abel; Abubakar, Ahmed; Achimugu, Augustina (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This study assessed the trends and variability of rainfall in Wukari, Nigeria, from 1981 to 2021, using the ECMWF ERA5 reanalysis data sets. Rainfall trends and variations over the study period were analyzed using Mann Kendal trend test and the Theil Sen slope estimator. The assessment of monthly rainfall variation for the rainy months (May-October) showed an increasing trend for August, September, and October, with August having the highest increasing trend of magnitude 0.051 mmmonth-1. The result also showed an encroachment of the dry spell towards the rainy season and vice versa. This will create a variation in onset of rainfall and cessation in the coming decades, which will affect the farming season in Wukari in terms of the time of planting and harvesting of crops. A decline in annual rainfall of magnitude -0.005mm/ year was observed within the period 1981 to 2021. The rainfall pattern revealed a periodic trend on a decadal basis with an increasing trend been followed be decreasing trend in the next decade. The highest increasing trend of magnitude 0.73 mmdecade-1 was observed in the third decade, and the highest decreasing trend in the fourth decade, with magnitude -0.93 mmdecade-1. Based on the trend pattern, an increasing trend in rainfall amount is expected in next decade (2021-2030), with a higher increasing trend magnitude greater than that of the third decade. Therefore, it is recommended that Government Agencies and stakeholders in the agriculture sector should be proactive in educating/enlightening farmers on the likelihood of a change in the farming season and make adequate preparation to mitigate the effect of flooding in the area.